Bioproses Penguraian Limbah Cair Buangan Industri Pangan dan Non-Pangan Berbasis Biosurfaktan - Yati Sudaryati Soeka; Joko Sulistyo (Bionature, 2022)
Biosurfactants are microbial metabolites that may be utilized to replace synthetic chemical surfactant inovercoming the problem of industrial wastewater pollution. Indications of the presence of biosurfactant activitymay be determined through measurement of emulsification and enzymatic activity of the tested microorganismson their growth media, which is indicated by decreasing the BOD and COD of the tested growth media containingwastewater material as an inducer added to the microbial growth medium. This research was conducted toexamine several potential microbial isolates that produce biosurfactants on growth media containing mixed wastewater. The results showed that some of the microbial cultures tested showed the potential to produce biosurfactantsas indicated by the emulsification and enzymatic activity of the tested microbial culture. Trial on mixed industrialwastewater showed that the tested biosurfactants were able to reduce the levels of BOD (440-1300 mg/l) and COD(1240-1760 mg/l) of the wastewater samples up to low BOD levels (82 mg/l) and COD (116 mg/l), respectively,thus that it meets the requirements of the established wastewater quality standards according to the IndonesianStandard regarding with the respective BOD (50-100 mg/l, 06-6989.9-2004 SNI) and COD (100-250 mg /l, 06-6989.2-2004 SNI).